Pergerakan Nasional dan Relevansinya Dalam Pembelajaran Sejarah Masa Kini - Ufie, Agustinus (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2020)
This paper theoretically examines, using a literature review method, the importance of building the nation's collective memory of the historical phenomenon 1908, which emerged from political, social, and cultural awareness and transformed into a spirit of unity that did not discriminate against one another at that time. The current reality shows deep concern because the spirit of diversity, harmony, and cohesion, the values of the national awakening, is gradually fading. The sense of nationalism during the national movement era provides authority that the nation's history is significant and should, therefore, be manifested through history education. In essence, education aims to build awareness, sympathy, and empathy towards past struggles. History education plays a crucial role in this, so teachers must be able to design various learning models that accommodate this goal. Amidst the chaos of politics, the escalation of conflicts and violence, and the loss of national identity, social phenomena that have weakened the foundations of our diversity, unity, and cohesion as a pluralistic nation must be addressed through the educational process.